Analysis Of Skills Needed for Examination of Child Witnesses / Victims in Police Investigating Offices - Fitriah, Aziza; Komalasari, Shanty; Ansyar, Ansyar (Technium Social Sciences Journal, 2022)
Skills are one of the most essential needs in carrying out work, including law enforcement officers who often interact with many people, especially when handling various legal cases. Law enforcement officials need skills in gathering information to obtain accurate data from witnesses and victims as a first step in handling the cases at hand. However, in fact, based on the results of preliminary observations and interviews conducted by researchers, law enforcement officials are considered to have experienced problems when extracting preliminary data for examining witnesses and victims of children aged 3 - 9 years. This is one of the obstacles that must be overcome and further analyzed in order to support the applicable legal process in order to be more optimal in its implementation. This research was conducted to determine the need for skills in the examination of witnesses and victims conducted by investigator-level law enforcement officers in Banjarmasin. Researchers used qualitative research methods using observation and interviews to collect data. The subjects in this study amounted to 3 law enforcement officers who stated they are willing to become research subjects. The results showed that law enforcement officers needed to improve their skills in handling witness and victim examinations, including skills in building rapport, empathetic communication, data collection techniques through accurate interviews, ability to read body language, and cognitive data mining techniques.